Accumulation and translocation of copper in Cu-polluted sierozem in northwest China. Issue 10 (24th August 2021) - Zang, Fei; Wang, Shengli; Chen, Yazhou; Nan, Zhongren; Zhao, Chuanyan
ABSTRACT: Studies on subsequent effects of Cu pollution on mineral nutrients uptake in different tissues of crops grown in sierozem are limited. A pot experiment was conducted to reveal the effects of exogenous Cu on the accumulation and translocation of Cu and the interaction with nutrients in different tissues of wheat in Cu-polluted sierozem in northwest China. Results showed that the average concentration of Cu in different tissues of wheat was roots > stems and leaves > grains > shells. The bioaccumulation factor (BCF) of Cu in different parts of wheat was roots > stems and leaves > grains > shells. There was a weak translocation of Cu from sierozem to tops of wheat. Furthermore, the translocation ability of Cu from roots to tops of wheat was increasingly weak with increasing Cu stresses. Micronutrients (Fe, Mn and Ca) distribution in different wheat tissues indicated that uptake and upward translocation of these kinds of micronutrients could be affected by high soil Cu concentration. The addition of Cu in sierozem promoted the Mn absorption in wheat tissues, which may also be helpful to solve the lack of Mn in wheat caused by the Cu shortage in sierozem.